PENINGKATAN AKSES AIR BERSIH MELALUI SOSIALISASI DAN PENYARINGAN AIR SEDERHANA DESA HAURPUGUR - Ratna Dian Kurniawati; Mariana Hanny Kraar; Vivit Nurul Amalia; M. Try Kusaeri (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat, 2020)
The use of clean water is one of the tagsets of Clean and Healthy Life Behavior (PHBS) for Households. Data from the Central Statistics Agency (BPS) states that the achievement of access to safe water in Indonesia has only reached 72.55%, below the Sustainable Development Goals (SDGs) target of 100%. Water for Hygiene Purposes Sanitation is water of a certain quality that is used for daily needs whose quality is different from the quality ofdrinking water. Haurpugur villagers use water that does not meet health requirements. Water in Haurpugur village tends to contain iron. Some of the water sources are dug wells. Where dug wells with an average depth of wells range from 10-15 meters. At these depths, the Fe and Mn contents settle to the bottom of the well. Most (55.8%) residents know well about the use of clean water. However, due to economic limitations, the fulfillment of cleanwater needs is ignored. In an effort to increase the knowledge of citizens and at the same time increase the coverage of clean water, it is necessary to carry out community service through socialization about clean water and making a simple filter of clean water. Achieving the fulfillment of clean water is a disease prevention limit that results from not fulfilling basic sanitation such as diarrhea.